The Hairpin Furans: Easily Prepared Hybrids of Helicenes and Twisted Acenes. (25th September 2015) - Geng, Xin; Donahue, James P.; Mague, Joel T.; Pascal, Robert A.
Abstract: The thermal reaction of a cyclopentadienone with 6, 6′‐dimethoxy‐5, 5′‐binaphthoquinone gives, in a single step, a molecular ribbon consisting of two twisted aromatic systems fused to a heteropentahelicene. Such molecules constitute a new class of chiral polycyclic aromatic compounds, the "hairpin furans". Abstract : Verdrehte Furane : In den Titelverbindungen ist ein Furanring zweifach mit chiralen molekularen Bändern aus einem verdrillten polycyclischen Aren kondensiert, sodass ein Heteropentahelicen resultiert. Die Verbindungen wurden durch eine einstufige Synthese hergestellt.